Efisiensi Dan Stabilitas Bank Umum Syariah Di Indonesia - Aam Slamet Rusydiana (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
The Islamic banking industry is currently one of the main indicators of the development of Islamic financial economics in general in Indonesia. This study tries to analyze the CCR and BCC models as a basic model in the DEA to see the level of efficiency of sharia commercial banks in Indonesia for the period 2007-2014. The results of the study conclude that the average efficiency of CRS as a whole from BUS in Indonesia is relatively low at 66%, while the average standard deviation is 0.14. This indicates the poor performance of the Sharia banking industry in general in Indonesia. Nevertheless, the VRS approach of Islamic banks has a higher efficiency value, namely 81%. For the analysis of bank groups with efficiency and stability efficiency criteria for VRS, there are 2 sharia commercial banks in quadrant 1 (high efficiency low stability), there are 4 Islamic banks in quadrant 2 (high efficiency and stability), and 3 Islamic banks into quadrant 3 (low efficiency and stability). Meanwhile there are 2 sharia commercial banks that are in the quadrant 4 category (low efficiency and high stability).